Formation of influenza virus particles lacking hemagglutinin on the viral envelope. - Pattnaik, A K (1986)
We investigated the intracellular block in the transport of hemagglutinin (HA) and the role of HA in virus particle formation by using temperature-sensitive (ts) mutants (ts134 and ts61S) of influenza virus A/WSN/33. We found that at the nonpermissive temperature (39.5 degrees C), the exit of ts HA from the rough endoplasmic reticulum to the Golgi complex was blocked and that no additional block was apparent in either the exit from the Golgi complex or post-Golgi complex transport. When MDBK cells were infected with these mutant viruses, they produced noninfectious virus particles at 39.5 degrees C. The efficiency of particle formation at 39.5 degrees C was essentially the same for both wild-type (wt) and ts virus-infected cells. When compared with the wt virus produced at either 33 or 39.5 degrees C or the ts virus formed at 33 degrees C, these noninfectious virus particles were lighter in density and lacked spikes on the envelope. However, they contained the full complement of genomic RNA as well as all of the structural polypeptides of influenza virus with the exception of HA. In these spikeless particles, HA could not be detected at the limit of 0.2% of the HA present in wt virions. In contrast, neuraminidase appeared to be present in a twofold excess over the amount present in ts virus formed at 33 degrees C. These observations suggest that the presence of HA is not an obligatory requirement for the assembly and budding of influenza virus particles from infected cells. The implications of these results and the possible role of other viral proteins in influenza virus morphogenesis are discussed.